Effects of Mitragynine on Locomotor and Anxiety in Rats Subjected to Restraint Stress - Adib Ridzuan, Nurul Raudzah (2010)
Mitragyna speciosa is an indigenous tree found in Southeast Asia particularly in Thailand and Malaysia. It is popularly known as ‘kratom’ in Thailand and ‘ketum’ in Malaysia. The medicinal properties of this plant were due to its opium-like effects and cocaine-like stimulant ability in combating fatigue and as hard work tolerance. The major alkaloid from this plant, mitragynine was extracted and isolated by solvent systems. Standard spectroscopic analysis was performed to identify the compound. Due to its potential properties as psychostimulant ability and anti-anxiety, this study was designed to determine the effects of mitragynine on locomotor activities and anxiety level in eustress and stress-induced rats. An effect of mitragynine on the corticosterone level was also determined. Locomotor and grooming activity in open-field test (OFT) and anxiety study in elevated plus-maze (EPM) were performed for the behavioral profiles. A hundred and sixty male Sprague-Dawley rats were used in the study and divided into two groups which were eustress and stress-induced rats. Mitragynine of different dosages (1.0, 5.0, 10.0 and 30.0 mg/kg) were administered intraperitoneally to each rat. Stress-induced rats were restrained for 2 hours in the restrainer before the behavioral activities were conducted. The findings showed that locomotor activity statistically increased (P<0.05) in 5.0 and 30.0 mg/kg mitragynine treated rats compared to 1.0 mg/kg mitragynine in non-stressed rats. Locomotor activity also increased in stressed-rats in all doses of mitragynine, however the results were not statistically significant. Grooming activity increased significantly (P<0.05) in stressed rats treated with 1.0, 5.0, 10.0 and 30.0 mg/kg mitragynine compared to control group. In non-stressed rats, grooming activity also increased in all doses of mitragynine but the results were not statistically significant. In anxiety study, three parameters were performed on each rat including time spent in open arms, open arm entries and time spent in central platform. Thirty (30.0) mg/kg mitragynine increased the time spent in open arms and open arm entries in non-stress and stress-rats. However, 30.0 mg/kg mitragynine decreased the time spent in central platform in non-stress and stress groups. Time spent in central platform only increased in non-stress rats treated with 5.0 and 10.0 mg/kg mitragynine. Corticosterone levels in stress-rats treated with all doses of mitragynine increased significantly (P<0.05) compared to control group. Higher dosages of mitragynine are able to induce behavioural changes by increasing the locomotor, grooming activity and anxiety parameters. Thus, the study showed that mitragynine produced sensitivity towards the locomotor, grooming and anxiety by increasing the parameters and is highly correlated with corticosterone levels in stressed rats. In conclusion, mitragynine is able to exert the possible psychostimulant and anxiolytic properties in non-stressed and stressed rats through the possible mechanism of action of mitragynine in rats.